Rechtsvacuum in Regional Regulations: Addressing the Gap in Tanah Ulayat Governance - Vena, Lymchya Nora; Yunarti, Sri; Octavia, Nurul Aini; Fitri, Hidayati (Institut Agama Islam Negeri Batusangkar, 2024)
The main issue discussed in this thesis is the rechtsvacuum in the protection of Tanah Ulayat rights in Nagari Palangki, Sijunjung District, and the implementation of West Sumatra Provincial Regulation No. 6 of 2008 in this area. The objective of this study is to explain and analyze the rechtsvacuum in the local government’s handling of customary land rights protection, as well as the application of the regulation regarding the utilization of customary land in Nagari Palangki. This research uses a field study approach with a normative and juridical-empirical analysis. The research findings indicate that a rechtsvacuum occurs when there is no regulation to address a specific case or event, creating uncertainty in the application of legal norms. In Nagari Palangki, the rechtsvacuum manifests in the lack of specific regulations regarding government buildings on customary land, leading to issues for future generations of the Kalumpang tribe, who are unable to clearly assert their rights. Furthermore, the implementation of West Sumatra Provincial Regulation No. 6 of 2008 has not been effective in Nagari Palangki. Based on the regulation, concrete steps to address this rechtsvacuum include the recognition of customary land rights, the formulation of local regulations, the empowerment of the Nagari community, and the resolution of land disputes.